Optimasi Konten Website SEO Friendly Bagi Persatuan Penyandang Difabel Indonesia (PPDI) Pekalongan - Dwi Budi Santoso; Jeffri Alfa Razaq; Fatkhul Amin (Intimas, 2023)
Abstract content between 150 – 200 words. The abstract is a summary of the article and should provide the important parts of the article. Abstracts can consist of background, problem formulation, proposed solutions, and implementation results. Abstract written using Cambria font size 10 pt (italic).